DIGITAL MARKETING TO E-COMMERCE CUSTOMERS - Nasaruddin Siregar; Sari Endah Nursyamsi; I Nyoman Tri Sutaguna; Geofakta Razali; Muhammad Yusuf (Journal of Management and Creative Business, 2023)
In this study, customer relationship management will be used as a mediating variable to examine the effects of digital marketing and trust on online purchase choices made by e-commerce customers in Bandung City. The participants or demographic in this study are online shoppers in Bandung City. For a structural equation model (SEM) that uses a formula of 9 times the number of indicator variables, which in this case is 138 samples, the requirement for selecting the number of samples is that it must be minimal. 1) Studies show that Bandung City's online purchasing behaviour, customer relationship management, digital marketing, and consumer trust are all satisfactory. 2) Customer relationship management in Bandung City is impacted by digital marketing for e-commerce. Trust is a factor in customer relationship management for e-commerce customers in Bandung City. 4) Online purchases made by Bandung City e-commerce customers are influenced by digital marketing.